PENINGKATAN KAPASITAS KEPEMIMPINAN TATA KELOLA KELURAHAN MELALUI PELATIHAN MANAJEMEN SUMBER DAYA MANUSIA (MSDM) - Riduan Siagian; Adrian K. Tarigan; Josua Tahan Jaya Sitorus (Jurnal Industri Kreatif dan Inovatif, 2025)
This Community Service Program (PKM) activity aims to improve leadership capacity in village governance through Human Resource Management (HRM) training. Partners' problems generally include non-competency-based task allocation, ineffective cross-functional coordination, weak discipline and performance standards, and minimal feedback and coaching mechanisms. The program is implemented through needs assessments, core training (public service leadership, communication, division of labor, simple KPIs, coaching), preparation of HRM governance tools (job desks, coordination SOPs, competency matrices, performance evaluation formats), and implementation assistance. Results show an increase in participants' understanding and managerial skills, the preparation of HRM governance documents for villages, and the existence of follow-up plans for improving service performance.